Effects of acute CDP-choline treatment on resting state brain oscillations in healthy volunteers. (30th March 2015) - Knott, Verner; Salle, Sara de la; Smith, Dylan; Choueiry, Joelle; Impey, Danielle; Smith, Meaghan; Beaudry, Elise; Saghir, Salman; Ilivitsky, Vadim; Labelle, Alain
Highlights: CDP-choline affects human brain oscillations. Oscillatory changes mimic nicotinic stimulation. These observations allow extensions to clinical populations. Abstract: CDP-choline (cytidine-5′-diphosphocholine) is a phospholipid used to treat cognitive disorders, presumably repairing and maintaining brain cell membranes. Additional mechanisms may include enhanced cholinergic neurotransmission as the α7 nicotinic receptor actions of choline and increased acetylcholine synthesis accompanying CDP-choline administration may modulate brain oscillations underlying cognitive processes. This study utilizes electroencephalographic (EEG) recordings in healthy volunteers to evaluate CDP-choline induction of an oscillatory response profile associated with nicotinic stimulation. Resting state EEG was acquired in 24 male volunteers administered low (500 mg) and moderate (1000 mg) doses of CDP-choline in a randomized placebo-controlled, crossover trial. Consistent with nicotinic agonist treatment, spectral analysis showed dose-dependent reductions in delta and increases in alpha oscillations, which were also accompanied by decreases in beta and gamma oscillatory activity. These findings support the posit that CDP-choline cognitive enhancement involves multiple mechanisms including facilitated nicotinic cholinergic action.